The Impact of Climate Change on Gender Roles in Semi-arid Agropastoral Communities: The Case of Kondoa District, Tanzania - Chawene, Agnes; Msongaleli, Barnabas; Mwanyoka, Iddi (Tanzania Journal for Population studies and Development, 2025)
Globally, the effects of climate change disproportionately affect agropastoral communities, with women being categorized as more vulnerable than men. However, information on how climate change affects the gender roles of agropastoral communities is limited in Tanzania. This study aims to assess the effects of climate change on gender roles among agropastoral communities in Kondoa District. The study employed a cross-sectional design. The data was gathered through household surveys, focus group discussions, and interviews with key informants. The SPSS (version 25) was employed to analyse quantitative data, while content analysis was used to analyse qualitative data. The study results showed that men and women were differently affected by climate change. The results also revealed that women were overburdened since they performed a variety of tasks, including walking long distances to collect firewood and water, handling all household chores, and milking and caring for young and sick livestock. Grazing was the primary activity that men handled, who also had to travel long distances to look for pastures and search for jobs away from home. Based on the results, gender roles in agropastoral communities are impacted by climate change in different ways. Therefore, the relevant organs addressing climate-related issues in local communities should consider gender-specific needs and vulnerabilities to improve mitigation and adaptation strategies.